Pengaruh Faktor Internal terhadap Kinerja Bisnis Koperasi Syariah (Survey terhadap unit Bisnis Koperasi Syariah di Bandung - Koernia Purwihartuti; Hennidah Karnawati; Tiafahmi Angestiwi; Kristianingsih Kristianingsih; Setiawan Setiawan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The main problems of sharia cooperatives are 47%capital, 35%decrease in sales, and 8%production barriers. Based on the results of previous studies, information was obtained that; (1) Sharia Cooperative Business Unit that grows during Pandemic is only a savings and loan while another business unit is declined dramatically and even almost loss, (2) Sharia cooperative members in Bandung are very varied, there are business people, rural residents who are technology blind, members of higher education, Private employees who have been technology literate that need adjustment in the service process, (3) The profit sharing system that characterizes sharia cooperatives requires openness to the conditions of the customer's financial performance. Currently it only relies on trust, (4) Limitations of Distribution due to government policies that limit the entry and exit of people to avoid the transmission of the Covid Virus 19. This study was conducted with the aim of: 1). Knowing the internal factors of Islamic cooperatives in Bandung; 2). Knowing the performance of Islamic cooperatives in Bandung; 3). Knowing the effect of internal factors on the performance of the Islamic cooperative business. The method used in this study is the Explanatory Survey. Data processing techniques are carried out with the help of PLS ​​3.2 to find out the internal factors that affect the performance of sharia cooperatives. This research was conducted with One Shoot Cross Sectional. The approach used is a combination of quantitative and qualitative approaches. The results showed that the internal factors of Islamic cooperatives consisted of marketing, operations, human resources, finance in the good category. Performance factors consisting of profit growth, cooperative services growth in good categories while cost growth in the category is quite good. There is an influence of 60.20 % internal factors on positive and significant business performance.